First in situ determination of the thermal performance of a U-tube borehole heat exchanger, in Cyprus - Florides, Georgios A.; Kalogirou, Soteris A. (My University, 2006)
A borehole heat exchanger can be used for the injection or extraction of thermal energy into/from the ground. One of the methods that can be used to determine the characteristics of a borehole Utube heat exchanger is the line source method which is simple and does not need expensive equipment. This method is explained and a test is performed in order to determine a borehole’s characteristics in layers consisting of clay, silt and sand at various analogies. For the borehole under test the ground thermal conductivity (λ) was found to be 2.7 W/(m K) and the effective borehole thermal resistance (Rb) to be 0.10 K/(W/m). The results of the test are very sensitive to the amount of initial data that are discarded. The test is also sensitive to the daily flux penetration through the ground which gradually increases the temperature of the top layers in summer and to the variation of the heating coil injection rate which affect the temperature of the fluid of the heat exchanger at some later time.
Keywords: Borehole; Earth heat exchanger; Thermal performance